Stratos N. Dordanas and Nikos Papanastasiou, eds., Ο «μακρύς» ελληνογερμανικός εικοστός αιώνας: Οι μαύρες σκιές στην ιστορία των διμερών σχέσεων [The “long” Greek-German twentieth century: The dark shadows in the history of the bilateral relationships] - Vachtsevanou, Chrysa (Historein, 2021)
Review of Stratos N. Dordanas and Nikos Papanastasiou, eds. Ο «μακρύς» ελληνογερμανικός εικοστός αιώνας: Οι μαύρες σκιές στην ιστορία των διμερών σχέσεων [The “long” Greek-German twentieth century: The dark shadows in the history of the bilateral relationships]. Thessaloniki: Epikentro, 2018. 488 pp.